2006
DOI: 10.1179/jmt.2006.14.4.88e
|View full text |Cite
|
Sign up to set email alerts
|

Physical Therapy Diagnosis and Management of a Patient with Chronic Daily Headache: A Case Report

Abstract: Chronic headaches are a significant health problem for patients and often a clinical enigma for the medical professionals who treat such patients. The purpose of this case report is to describe the physical therapy diagnosis and management of a patient with chronic daily headache. The patient was a 48-year-old woman with a medical diagnosis of combined common migraine headache and chronic tension-type headache. An exacerbation of these long-standing headache complaints had resulted in a chronic daily headache … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 128 publications
(202 reference statements)
1
5
0
Order By: Relevance
“…Trigger points in the head and neck region have been implicated in the reported headache and central sensitization in patients with tension-type headache. Their referral patterns correspond to the pain characteristics and distribution reported by patients with cervicogenic headache, occipital neuralgia, and migraine headache 3 . Studies have reported signifi cantly greater numbers of active MTrPs in the suboccipital muscles of patients with tension-type headache and in patients with migraine headache when compared to asymptomatic controls [14][15][16] .…”
Section: Immediate Effects Of Inhibitive Distraction On Active Range supporting
confidence: 72%
See 1 more Smart Citation
“…Trigger points in the head and neck region have been implicated in the reported headache and central sensitization in patients with tension-type headache. Their referral patterns correspond to the pain characteristics and distribution reported by patients with cervicogenic headache, occipital neuralgia, and migraine headache 3 . Studies have reported signifi cantly greater numbers of active MTrPs in the suboccipital muscles of patients with tension-type headache and in patients with migraine headache when compared to asymptomatic controls [14][15][16] .…”
Section: Immediate Effects Of Inhibitive Distraction On Active Range supporting
confidence: 72%
“…In a cross-sectional population survey, Guez et al 2 found an 18% prevalence for chronic neck pain (>6 months' duration). Headache types associated with cervical spine dysfunction include tensiontype and cervicogenic headache, occipital neuralgia, and-to a lesser extent-migraine headaches 3 . Tension-type headache affects two-thirds of men and over 80% of women in developed countries 4 .…”
Section: Immediate Effects Of Inhibitive Distraction On Active Range mentioning
confidence: 99%
“…The N=1-trial and also less methodologically rigorous case reports and case series are clinic-friendly designs that help construct our evidence pyramid. I have enjoyed reading the recent examples of this type of design published in JMMT 45,46 . My suggestion is to critically evaluate the evidence pyramid for different areas of MPT.…”
Section: Use Of the "Inverse Evidence Pyramid"mentioning
confidence: 99%
“…Temporomandibular joint disorder is a functional disturbance. Temporomandibular joints, masticatory muscles, teeth, bones and the central nerve system are all involved in TMJ pathology [3][4][5][6]. For many years, clinicians have employed various mechanical tools for diagnosis and to understand the reasons for the problem [7].…”
Section: Introductionmentioning
confidence: 99%
“…It has been advocated in textbooks on occlusion [2,3,[5][6][7] that mark area is a representative of the load contained within the mark. Legends to photographs depicting occlusal adjustment technique end results and paper mark appearance describe that large and dark marks indicate heavy load, and that smaller and light marks indicate lesser loads [5][6][7].…”
mentioning
confidence: 99%